ANALISA PEMILIHAN PLATFORM JASA PEMESANAN MAKANAN ONLINE METODE SAW - Melati, Melati; Putri, Sukmawati Anggraeni (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2023)
Technology and Information is growing, including Information Technology in online food ordering service platforms. The presence of an online food ordering service platform is a means of connecting and technology that provides convenience for food entrepreneurs and consumers. Where Gofood, Grabfood, and Shopeefood are platforms that are often used by most people at this time. The growing number of online food ordering service platforms, makes it difficult for consumers to choose which platform provides a lot of convenience. Starting from delivery fees, discounted prices, speed of delivery and which platforms provide many restaurants. Therefore, the purpose of this research is to provide information to consumers or users of the online food ordering service platform to determine the best online food ordering service platform by applying calculations using the Simple Additive Weighting (SAW) method. Based on data collected through questionnaires, and through calculations using the Simple Additive Weighting (SAW) method, the best online food ordering service platform is Shopee food.